1981
DOI: 10.1111/j.1469-185x.1981.tb00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Phycology and Heavy‐metal Pollution

Abstract: Summary 1. All heavy metals, including those that are essential micronutrients (e.g. copper, zinc, etc.), are toxic to algae at high concentrations. 2. One characteristic feature of heavy‐metal toxicity is the poisoning and inactivation of enzyme systems. Many of the physiological and biochemical processes, viz., photosynthesis, respiration, protein synthesis and chlorophyll synthesis, etc., are severely affected at high metal concentrations. 3. Some algae inhabit waters chronically polluted with heavy‐metal‐l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
167
0
3

Year Published

1983
1983
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 405 publications
(177 citation statements)
references
References 146 publications
(125 reference statements)
7
167
0
3
Order By: Relevance
“…These extracellular polysaccharides also contain ligands which can bind metal ions (Rai et al, 1981). Microbes such as Pseudomonas (Gamma Proteobacteria), and Citrobacter (Omnibacteria) also produce large quantities of extracellular polysaccharides (Liu and Wu, 1993;Marques et al, 1990), which can complex U.…”
Section: Adsorptionmentioning
confidence: 99%
“…These extracellular polysaccharides also contain ligands which can bind metal ions (Rai et al, 1981). Microbes such as Pseudomonas (Gamma Proteobacteria), and Citrobacter (Omnibacteria) also produce large quantities of extracellular polysaccharides (Liu and Wu, 1993;Marques et al, 1990), which can complex U.…”
Section: Adsorptionmentioning
confidence: 99%
“…Microalgal cultures offer an elegant solution to tertiary and quinary treatments due to the ability of microalgae to use inorganic nitrogen and phosphorus for their growth (Richmond, 1986;Oswald, 1988b,c;Garbisu et al, 1991Garbisu et al, , 1993Tam and Wong, 1995). And also, their capacity to remove heavy metals (Rai et al, 1981), as well as some toxic organic compounds (Redalje et al, 1989), therefore, does not lead to secondary pollution. Amongst beneficial characteristics they produce oxygen, have a disinfecting effect due to increase in pH during photosynthesis (Mara and Pearson, 1986;De la Nou¨e and De Pauw, 1988).…”
Section: Microalgae For Wastewater Treatmentmentioning
confidence: 99%
“…Microalgal cultures offer an elegant solution to tertiary and quaternary treatments due to the ability of microalgae to use inorganic nitrogen and phosphorous for their growth (Oswald, 1988b,c;Richmond, 1986) and their capacity to remove heavy metals (Rai et al, 1981). Lau et al (1996) studied the ability of Chlorella vulgaris in nutrients removal and reported a nutrient removal efficiency of 86% for inorganic N and 78% for inorganic P. In earlier study, Colak and Kaya (1988) reported an elimination of nitrogen (50.2%) and phosphorus (85.7%) in industrial wastewater treatment and elimination of phosphorus (97.8%) in domestic wastewater treated by algae.…”
Section: Removal Of N And/or Pmentioning
confidence: 99%
“…Colby's formula, reviewed by Rai et al [37], was applied to the response data for calculating the expected combined toxicity of the PAH and heavy metal cocontamination. The formula was first derived by Colby in 1967 and reviewed by Rai et al [37] in 1981, based on the assumptions that the chemicals act consecutively on the organism.…”
Section: Combined Toxic Effects Of Mixed Pahs and Heavy Metalsmentioning
confidence: 99%
“…The formula was first derived by Colby in 1967 and reviewed by Rai et al [37] in 1981, based on the assumptions that the chemicals act consecutively on the organism. This formula was used to estimate the type of binary interaction by statistical testing of the null hypothesis of additive toxicity, based on multiplication of the response of the control when exposed to one toxicant and the response of the control when exposed to another toxicant.…”
Section: Combined Toxic Effects Of Mixed Pahs and Heavy Metalsmentioning
confidence: 99%